Kedudukan Jaksa Penuntut Umum Dalam Sistem Peradilan Pidana - Simamora, Feri Sanro; Manullang, Herlina (Innovative: Journal Of Social Science Research, 2024)
The position of the Public Prosecutor in the criminal justice system is very important as a representative of the state in law enforcement. The main role of the Prosecutor is to prosecute criminal cases that occur, ensuring that justice is served and the public is protected from criminal acts. As the party responsible for the prosecution, the prosecutor plays a role in collecting evidence, preparing charges, and presenting arguments in court. In carrying out their duties, the Public Prosecutor must uphold the principles of justice, transparency and accountability. They have an obligation to not only pursue punishment for defendants, but also to protect individual rights and ensure that the judicial process is conducted fairly. This includes the obligation to objectively evaluate whether the available evidence is sufficient to prove the defendant's guilt. Prosecutors also play a role in the mediation process and settling cases outside of court, providing alternatives that can reduce the burden on the justice system. In this context, the position of prosecutors is very strategic, because they are between the public interest and the rights of the defendant. Therefore, Public Prosecutors must have high integrity, good analytical skills, and a deep understanding of the law to carry out this role effectively and be responsive to developing social dynamics. Through this position, the Public Prosecutor contributes to building public trust in the criminal justice system.